1992
DOI: 10.1111/j.1398-9995.1992.tb02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Local nasal immunotherapy in allergic rhinitis to Parietaria

Abstract: Preseasonal local nasal immunotherapy (LNIT) by means of an extract in macronized powder form has been studied in allergic rhinitis to parietaria. Twenty-four Parietaria-sensitive patients have been studied for 18 weeks in a double-blind controlled trial. Subjects were selected on the basis of a positive skin test, RAST and intranasal challenge to Parietaria antigen. Three eight-patient groups were randomly planned: the first group was given native Parietaria product, the second modified Parietaria product, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 21 publications
(22 reference statements)
0
41
0
Order By: Relevance
“…So far, 21 studies are available for LNIT, and 14 of them were properly performed (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Of these, 13 report a significant improvement of rhinitic symptoms. Furthermore, a reduction of the nasal reactivity and local immunologic response was found in some studies, while systemic immunologic changes were usually absent or equivocal: this may suggest that LNIT exerts its actions only on the target organ.…”
Section: Experimental Evidence: Clinical Efficacymentioning
confidence: 99%
“…So far, 21 studies are available for LNIT, and 14 of them were properly performed (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Of these, 13 report a significant improvement of rhinitic symptoms. Furthermore, a reduction of the nasal reactivity and local immunologic response was found in some studies, while systemic immunologic changes were usually absent or equivocal: this may suggest that LNIT exerts its actions only on the target organ.…”
Section: Experimental Evidence: Clinical Efficacymentioning
confidence: 99%
“…The first involved subcutaneous injections of an alginate-conjugated extract [24]. The second used nasal inhalations of an extract in macronized powder form [25]. Because demonstrations of efficacy for one allergen or one allergenic extract do not necessarily mean that efficacy will occur with other allergens or extracts there is a clear need for carefully controlled studies demonstrating such efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…On the same topic, Andri et al [19] showed that LNIT using an extract in macronized powder form reduced drug consumption in allergic rhinitis to Parietaria. LNIT with aqueous ragweed extract was clinically effective, with a dose-relation [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%